Musculoskeletal Pain Description in Adolescence with Internet Addiction: Community Engagement in Senior High School - Sunarjo, Peggy; Budiati Laksmitasari; Fitri Anestherita; Rizky Kusuma Wardhani; Melinda Harini; Steven Setiono; Ibrahim Agung (Surabaya Physical Medicine and Rehabilitation Journal, 2024)
Background: Some bad postures resulting from bad habits that had lasted since childhood, especially posture while accessing internet using gadget, might lead to some complications in adolescence. Aim: In this community engagement program, we tried to explore internet addiction and musculoskeletal pain proportions in some students. Material and methods: This is a cross-sectional study conducted in a senior high school at Jonggol, West Java, in February 2023. Students were gathered to have an education class about good posture. Before the education session, we asked the students to explore whether they had internet addiction and musculoskeletal pain by filling out the Indonesian Internet Addiction Diagnostic Questionnaire and Cornell Musculoskeletal Discomfort Questionnaire. Results: Thirty-nine students were involved in this study. As many as 19 (48.7%) students have an internet addiction. More than 50% of the addicted students often have moderate-severe pain in their neck, back and right wrist and reported that the pain interferes with their daily activities. Conclusions: Almost half of students attending posture education class had internet addiction and musculoskeletal pain. A further study with a larger sample size needs to be conducted to show the correlation between internet addiction and musculoskeletal pain in adolescence and other factors that correlate with them.